Review of the Role of Orphan Crops in Food Security - Feyisa, Ashebir Seyoum (Research on World Agricultural Economy, 2022)
Ethiopia is one of the most populated countries in Africa. Agriculture employs over 70% of the population. It is dominated by small-scale farmers who practice rain-fed mixed farming by using traditional technology, adopting a low input and low output production system. As a result, it is vulnerable to adverse weather conditions. Cereal crops provide food for the majority of Ethiopians, so most agricultural transformation plans prioritize increasing cereal crop productivity. However, about five million people experience food insecurity each year and require support. Population growth, environmental degradation, conflict, and climate change are the most serious threats to the nation’s food security. In a time when the food supply cannot keep up with population expansion, there is a need for holistic solutions to development-related issues such as food insecurity, malnutrition, and poverty. Despite Ethiopia being a center of origin and diversity for several food crops, the potential benefits of underutilized indigenous crops are yet not exploited. However, they can play a significant part in human nutrition, income, and medicinal value. As a result, crop diversification may be the best choice for achieving household food security. One way to help the nation’s food systems diversify is to include more orphan crops. Even though a small portion of the country’s land is dedicated to underused crops, more than 20% of the population relies on them for food. Orphan crops, such as inset, which can feed 100 million people, can help to attain food security in Ethiopia. As a result, promoting and researching these crops is the most sustainable strategy for lowering and managing poverty and food insecurity in Ethiopia. ER